(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the reflection of Eastern spirituality and philosophy in the works of the English Romantic poet Lord Byron. The study analyzes Byron’s interest in the East and its influence on his works. The article considers Byron’s "Oriental Tales," as well as works such as "The Giaour" and "Don Juan." The results indicate that Eastern spirituality and philosophy left a profound mark on Byron’s works, leading to the creation of multifaceted Eastern images in his poetry and prose.